Highly stable adamantyl-substituted pincer-ligated iridium catalyst for alkane dehydrogenation - Punji, Benudhar; Emge, Thomas J.; Goldman, Alan S. (Organometallics, 2010)
The adamantyl-substituted pincer-ligand precursor AdPCP-H [(AdPCP = κ3-C6H3-2,6-(CH2PAd2)2); Ad = 1-adamantyl] has been synthesized by the reaction of 1,3-dibromoxylene with di-1-adamantylphosphine in the presence of triethylamine. Treatment of AdPCP-H with [Ir(COD)Cl]2 (COD = 1,5-cyclooctadiene) affords the pincer-ligated complex (AdPCP)IrHCl, which was crystallographically characterized. Dehydrohalogenation of (AdPCP)IrHCl either with LiBEt3H or with KOtBu, under hydrogen atmosphere, yields the hydrides (AdPCP)IrH2 and (AdPCP)IrH4. (AdPCP)IrH2 catalyzes dehydrogenation of alkanes with a level of activity comparable to that of the previously reported (tBuPCP)IrH2, while it is thermally much more robust than the tBuPCP analogue, as well as iPrPCP or tBuPOCOP pincer complexes.